Democratic Republic of Congo: Country brief - HarvestPlus (International Food Policy Research Institute, 2015)
HarvestPlus improves nutrition and public health in the Democratic Republic of Congo (DRC) by promoting cassava that provides more vitamin A and beans that provide more iron in the diet. We work with more than 200 partners drawn from government, business, and civil society.